2012
DOI: 10.3109/15563650.2012.718783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pirfenidone on pulmonary fibrosis due to paraquat poisoning in rats

Abstract: This study showed that pirfenidone is able to decrease pulmonary fibrosis following paraquat poisoning in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…It has been shown that increased oxidative stress could enhance prevalence of malignancies by direct cellular damage, Seifirad et al (2012); Lu et al (2013); Seifirad and Masoudkabir (2013) however, as mentioned above oxidative stress when applied as immune system arms could protect organisms from invading pathogens and malignant cells (Weel et al, 1996). …”
Section: Oxidative Stress: a Double-edged Swordmentioning
confidence: 99%
“…It has been shown that increased oxidative stress could enhance prevalence of malignancies by direct cellular damage, Seifirad et al (2012); Lu et al (2013); Seifirad and Masoudkabir (2013) however, as mentioned above oxidative stress when applied as immune system arms could protect organisms from invading pathogens and malignant cells (Weel et al, 1996). …”
Section: Oxidative Stress: a Double-edged Swordmentioning
confidence: 99%
“…Immediate treatment with anti-oxidants (such as vitamins C and E), glucocorticoids, cytotoxic agents and certain forms of newly developed antifibrotic agents can improve the prognosis [10]. Only recently have radiological findings, such as CT scanning, been employed to examine the pulmonary effects and progression of acute PQ poisoning, revealing the highly variant response of individual patients to PQ.…”
mentioning
confidence: 99%
“…Vitamin C chromium-induced pulmonary fibrosis prevents pulmonary fibrosis in rats and its combination with vitamin E is more effective [28]. On the other hand, it was determined that vitamin C is not effective in preventing fibrosis created with paraquat [29]. It was shown that nonalcoholic steatohepatitis-related fibrosis decreases in patients when a vitamin C and vitamin E combination is applied compared to placebo.…”
Section: Discussionmentioning
confidence: 99%